Anthropometric-morphologic, psychomotor, energetic and technical tactic features of sailors in Olympic classes - Lozovina, M.; Dukic, N. (Sport Science - International Scientific Journal of Kinesiology, 2017)
Sports sailing Olympic class, in this paper, we approached analyzing some previous research anthropological characteristics sailors in these classes, and attention is paid to antropometric-morphological space, space of psychomotor abilities, energetic components, expressed through aerobic and anaerobic work sailors as well as technical and tactical features sailors in the Olympic classes, the areas that are most often researched and presented in national and international scientific literature. Analyzed areas would have no purpose if they are not placed in the context of the theory of sports training sailors, we work presented theoretical foundations of training status and form of sailors as well as planning and programming of training in the sport sailing. Considering the shortcomings and inadequacy of scientific papers in the cultivated areas of anthropological status of sailors in the Olympic classes in the work we have put forward relevant information to all those who are sailing with, and scientists sent a message and are directed towards the scientific approaches that will lead to work with in practice usable results.